EFEKTIVITAS MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) BERBANTUAN MEDIA INFOGRAFIS TERHADAP KREATIVITAS TERMODINAMIKA KELAS XI SMA NEGERI 13 TAKALAR - Auliya, Musfira; Muhammad Yusuf Hidayat; Andi Ferawati Jafar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine students’ creative thinking levels before and after the implementation of the Project Based Learning (PjBL) model assisted by infographic media, and to examine the improvement of creative thinking skills in thermodynamics learning among class XI students at SMA Negeri 13 Takalar. This research employed an experimental method using a One Group Pre-Test Post-Test Design. The population consisted of all class XI students at SMA Negeri 13 Takalar, while the sample included one class of 26 students selected through purposive sampling. The research instruments were a creative thinking test administered as a pretest and posttest, and an observation sheet used to monitor students’ activities during the learning process. Data were analyzed using descriptive statistical analysis and the N-Gain test to measure the improvement in students’ creative thinking skills. The findings revealed that students’ creative thinking levels before the implementation of the PjBL model assisted by infographic media were categorized as low, with an average score of 39.07. After the implementation of the learning model, the average posttest score increased to 75.35, indicating a creative category. Furthermore, the N-Gain analysis produced an average score of 0.56, categorized as moderate, showing that the learning model effectively improved students’ creative thinking skills. Therefore, the results of this study can serve as a reference for teachers and future researchers in applying PjBL assisted by infographic media. This approach also encouraged active participation, collaboration, and better understanding of thermodynamics concepts during classroom learning activities among students at school.